Complete mitochondrial genome of the marine monogonont rotifer Proales similis (Rotifera, Proalidae) - Beom-Soon Choi; Young Hwan Lee; Jin-Sol Lee; Takahiro Yamade; Atsushi Hagiwara; Jae-Seong Lee (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome was sequenced from the marine monogonont rotifer Proales similis. The size of mitochondrial genome sequences was 16,819 bp and all the genes were unidirectional on the same strand. Of 12 protein-coding genes (PCGs), two genes (ND5 and ND2) had incomplete stop codons TG (for ND5) and T (for ND2). Furthermore, the start codon of all the genes was ATG, while the stop codons were TAA, TAG, and TGA. The base composition of 12 PCGs in P. similis mitogenome showed 20.8% for A, 47.0% for T, 17.4% for C, and 14.8% for G, respectively. The mitochondrial genome A + T base composition (67.8%) of 12 PCGs was higher than G + C (32.2%), while the complete mitochondrial genome A + T base composition (67.2%) was higher than G + C (32.8%).